Safety, Tolerability and Immunogenicity of an MF59-adjuvanted, Cell Culture-derived, A/H5N1, Subunit Influenza Virus Vaccine: Results From a Dose-finding Clinical Trial in Healthy Pediatric Subjects. Issue 7 (July 2019) - Chanthavanich, Pornthep; Anderson, Edwin; Kerdpanich, Phirangkul; Bulitta, Michael; Kanesa-thasan, Niranjan; Hohenboken, Matthew
Abstract : Background: A/H5N1 influenza virus has significant pandemic potential, and vaccination is the main prophylactic measure. This phase 2, randomized, observer-blind, multicenter study evaluated the safety and immunogenicity of two MF59-adjuvanted, cell culture-derived H5N1 (aH5N1c) vaccine formulations in healthy pediatric subjects 6 months to 17 years old. Methods: Subjects (N = 662) received 2 aH5N1c doses 3 weeks apart, containing either 7.5 μg (full dose) or 3.75 μg (half dose) hemagglutinin antigen per dose. Local reactions and adverse events (AEs) were assessed by age. Antibody responses were measured by hemagglutination inhibition assay and assessed as geometric mean titers, geometric mean ratios (GMRs) and percentages of subjects achieving titers ≥1:40 and seroconversion (NCT01776554). Results: No vaccine-related serious AEs occurred. Incidence of solicited local reactions and systemic AEs were similar across vaccine groups. Tenderness and irritability in <6-year olds, and injection site pain, myalgia and fatigue in 6–17-year olds were the most commonly reported reactions in both full- and half-dose recipients. Frequencies of AEs were lower after the second dose than the first dose in all vaccine and age groups. Three weeks after the administration of a second dose, both full- and half-dose formulations met the Center for Biologics Evaluation Research and Review (United States) and Committee for Medicinal Products for Human Use (EU) licensure criteria for titers ≥1:40 (full dose 96% subjects; half dose 86%), seroconversion (full dose 96% subjects; half dose 86%), and GMR (full dose GMR 262; half dose 84). Antibody responses were highest in 6–35-month olds. Conclusions: In pediatric subjects, both aH5N1c vaccine formulations were well tolerated and highly immunogenic, meeting both US and EU licensure criteria for pandemic influenza vaccines. Abstract : Supplemental Digital Content is available in the text.